Mutualizing Euro Area debt without a Fiscal Union - Krause Montalbert, Stefan (2018)
Several years have passed since the onset of the most recent financial crisis, and Europe is still not “off the hook.”  A twin crisis emerged: the sovereign debt crisis.  The main objective of this paper is to design a mechanism for pooling Euro Area debt together, in order to lower short-term interest rates, and limit the risk of contagion.  This design, which draws from existing proposals for jointly issued bonds in the Euro Area, contains features that would make it acceptable for participants (such as no ex-ante fiscal transfers across countries, and widespread benefits from lower debt-service payments), while placing a reasonable cap on potential losses from default by other participants through limited liability.